If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2x + 6 = 9x + 2 Reorder the terms: 6 + 5x + 2x = 9x + 2 Combine like terms: 5x + 2x = 7x 6 + 7x = 9x + 2 Reorder the terms: 6 + 7x = 2 + 9x Solving 6 + 7x = 2 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 6 + 7x + -9x = 2 + 9x + -9x Combine like terms: 7x + -9x = -2x 6 + -2x = 2 + 9x + -9x Combine like terms: 9x + -9x = 0 6 + -2x = 2 + 0 6 + -2x = 2 Add '-6' to each side of the equation. 6 + -6 + -2x = 2 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = 2 + -6 -2x = 2 + -6 Combine like terms: 2 + -6 = -4 -2x = -4 Divide each side by '-2'. x = 2 Simplifying x = 2
| 2x+16=3x+7 | | -x+6(-4)=1 | | 4x+8=6x+2 | | 28/16=x/12 | | 9x+4=-5+2x+23 | | 9x+4=-52x+23 | | 28x=192 | | 8-7x-3=-26+4x-13 | | 7xy+3y=-22 | | -6a=-4 | | 5x+23=3+8x-7 | | 6x+30y=238 | | 1e+8=2e-12 | | 6x-1=4x+33 | | (4-6x)/(x^2+3x-10)=-2 | | 2x+18y=138 | | -3x-8=7x+22 | | 360h=3290 | | x^2/(x+1)/(x-1)=-2 | | 35=x | | 13y+22= | | 1/2(35)=x | | 63-7x=21x+20 | | 81-2x=-11x | | 0.4x+7.6=6.2 | | 0.9(x+60)+0.1x=79 | | 6x-1=5x+4 | | -10n=2/3 | | (2x-4)/(x+5)=-3 | | -11-4=-9/4n | | (2x-4)/(x+5)=1 | | -20-(-46)=x/12 |